Descriptive analysis study of prose poetry in Mahmoud Darwish poetry (Yawmiyyat Athar Al-Farashah) - Alhoot, Hana Abdulfatah Mosa (Tanjong Malim, 2020)
Descriptive analysis study of prose poetry in Mahmoud Darwish poetry (Yawmiyyat Athar Al-Farashah) by Alhoot, Hana Abdulfatah Mosa